Roles of Renal Proximal Tubule Transport in the Pathogenesis of Hypertension - Horita, Shoko; Seki, George; Yamada, Hideomi; Suzuki, Masashi; Koike, Kazuhiko; Fujita, Toshiro (Current Hypertension Reviews, 2013)
Hypertension is a key factor of cardiovascular disease. Many organs and systems including heart, blood vessel, kidney, sympathetic nerve, and endocrine systems are involved in the regulation of blood pressure. In particular, the kidney plays an essential role in the regulation of blood pressure, but is also quite vulnerable to hypertensive tissue damage. For example, most chronic kidney disease (CKD) patients have hypertension and are revealed to have higher mortality than normal population. Furthermore, hypertensive renal sclerosis is emerging as the third main cause of dialysis patients. This mini review is to summarize the effects of angiotensin II and dopamine on renal proximal tubule transport, which may have important roles in the regulation of blood pressure.
Keywords: hypertension